Comparative study of sealing ability of three root canal sealers - Khedmat S.; Rezaeifar M. (Tehran University of Medical Sciences, 2007)
Background and Aim: Complete obturation of the prepared root canal is an essential step in endodontic treatment. Combination of gutta-percha and a sealer is widely used in clinical practice for root canal obturation, thus microleakage studies on sealing properties of these materials constitute an important part of endodontic researches. The aim of this study was to evaluate the microleakage of three root canal sealers: Apexit, AH26 and Dorifill by electrochemical method.Materials and Methods: In this experimental study, 55 extracted human maxillary and mandibular cuspids were used. The coronal part of teeth were removed and the root canals were prepared using the step-back technique. The specimens were randomly divided into 3 groups of 17 samples each. Teeth in each group were filled with one of the sealers and gutta-percha by lateral condensation technique. 4 specimens served as positive and negative controls. An electrochemical method was used for evaluation of apical leakage with the electrical source potential of 10 V. Measurements of current flow through the test system were recorded every 72 hours. Data were analyzed by Kruskall Wallis and Mann Whitney tests. P<0.05 was considered as the level of significance.Results: All specimens of the three groups showed low initial leakage that increased during the test period. The mean leakage in Apexit group was higher than AH26 and Dorifill groups. The lowest mean leakage was related to Dorifill group. Although no statistically significant difference was observed between this sealer and AH26.Conclusion: The results of this study revealed that the best apical seal was obtained using Dorifill and AH26 sealers. The poorest result was observed in Apexit.